The Genome Russia project: closing the largest remaining omission on the world Genome map. Issue 1 (December 2015) - Oleksyk, Taras; Brukhin, Vladimir; O'Brien, Stephen
Abstract We are witnessing the great era of genome exploration of the world, as genetic variation in people is being detailed across multiple varied world populations in an effort unprecedented since the first human genome sequence appeared in 2001. However, these efforts have yet to produce a comprehensive mapping of humankind, because important regions of modern human civilization remain unexplored. The Genome Russia Project promises to fill one of the largest gaps, the expansive regions across the Russian Federation, informing not just medical genomics of the territories, but also the migration settlements  of historic and pre-historic Eurasian peoples.